2015
DOI: 10.1080/2162402x.2015.1051297
|View full text |Cite
|
Sign up to set email alerts
|

GITR engagement in combination with CTLA-4 blockade completely abrogates immunosuppression mediated by human liver tumor-derived regulatory T cellsex vivo

Abstract: Sprengers (2015) GITR engagement in combination with CTLA-4 blockade completely abrogates immunosuppression mediated by human liver tumor-derived regulatory T cells ex vivo, OncoImmunology, 4:12, e1051297, DOI: 10.1080/2162402X.2015 Keywords: cytotoxic T lymphocyte-associated antigen 4 (CTLA-4), glucocorticoid-induced tumor necrosis factor receptor (GITR), hepatocellular carcinoma (HCC), liver metastases from colorectal cancer (LM-CRC), regulatory T cells (Treg)In liver cancer tumor-infiltrating regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…As a consequence, tumor-infiltrating Treg, 40 , 41 type 1 regulatory T cells 52 and probably other types of immune suppressor cells were also present in these assays. Therefore, the reported functional effects of checkpoint inhibitors on effector T cells in these assays may be partly indirect, mediated by effects of these antibodies on suppressor cells.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…As a consequence, tumor-infiltrating Treg, 40 , 41 type 1 regulatory T cells 52 and probably other types of immune suppressor cells were also present in these assays. Therefore, the reported functional effects of checkpoint inhibitors on effector T cells in these assays may be partly indirect, mediated by effects of these antibodies on suppressor cells.…”
Section: Discussionmentioning
confidence: 90%
“…40 , 41 Myeloid dendritic cells (mDC) were isolated from patient autologous PBMC by depletion of CD19 + B cells followed by positive selection for BDCA-1 (BDCA-1 DC isolation kit, Miltenyi Biotec). mDC were cultured overnight with or without 20 µg/mL autologous tumor lysates or normal liver lysates, in the presence of 10 ng/mL granulocyte-macrophage colony-stimulating factor (Miltenyi Biotec) and 0.5 µg/mL polyinosinic: polycytidylic acid (InvivoGen, San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that engagement of GITR by GITRL reduced the suppression that HCC tumor‐derived Treg exert on blood‐derived CD4 + CD25 − T cells in ex vivo cultures . We now evaluated whether GITR ligation can enhance effector responses of HCC‐derived CD4 + and CD8 + TIL.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to co‐inhibitory interactions, and to high numbers of conventional CD4 + FoxP3 + CD25 + regulatory T cells (Treg) and type 1 regulatory T cells present in liver tumors, which inhibit functions of effector T cells. We also demonstrated that agonistic targeting of GITR can alleviate the suppressive capacity of liver tumor‐derived CD4 + CD25 + Treg . However, the expression of GITR on cytotoxic CD8 + tumor‐infiltrating lymphocytes (TIL) and CD4 + FoxP3 − T helper cells (Th) in HCC patients is unknown.…”
Section: Introductionmentioning
confidence: 96%